2021
DOI: 10.1039/d1fo02391h
|View full text |Cite
|
Sign up to set email alerts
|

Dietary agents in mitigating chemotherapy-related cognitive impairment (chemobrain or chemofog): first review addressing the benefits, gaps, challenges and ways forward

Abstract: Chemobrain or chemofog is one of the important but less investigated side effects, where the cancer survivors treated with chemotherapy develop long-term cognitive impairments, affecting their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 212 publications
0
3
0
Order By: Relevance
“…Our results working with the modulator of the nAChRs, Cotinine, acting as a positive allosteric modulator of the α7nAChRs enhanced contextual fear memory extinction without altering the acquisition and short-term retention of fear memory in a nAChR dependent-manner ( Lotfipour et al, 2013 ). Based on th current evidence, we have postulated that cotinine-induced enhancement of extinction is mediated by increased neuronal plasticity and neurogenesis in rodents ( Echeverria et al, 2017 ; Sadigh-Eteghad et al, 2020 ; Bastianini et al, 2021 ; Raghu et al, 2021 ). Few years ago, Sadigh-Eteghad et al (2020) found that chronic cotinine ameliorated learning and memory in aged animals in the MWM and novel object recognition (NOR) tasks ( Sadigh-Eteghad et al, 2020 ), and also increased the expression of (a) antioxidant factors such as the superoxide dismutase (SOD), (b) synaptic proteins (PSD95, GAP-43, and synaptophysin), (c) neurotrophic factors brain-derived neurotrophic factor (BDNF), and neural growth factor (NGF), while decreasing cytokines (TNFα and IL1β) in the hippocampus of aged mice ( Sadigh-Eteghad et al, 2020 ).…”
Section: Role Of the Nachrs In Learning And Memorymentioning
confidence: 99%
“…Our results working with the modulator of the nAChRs, Cotinine, acting as a positive allosteric modulator of the α7nAChRs enhanced contextual fear memory extinction without altering the acquisition and short-term retention of fear memory in a nAChR dependent-manner ( Lotfipour et al, 2013 ). Based on th current evidence, we have postulated that cotinine-induced enhancement of extinction is mediated by increased neuronal plasticity and neurogenesis in rodents ( Echeverria et al, 2017 ; Sadigh-Eteghad et al, 2020 ; Bastianini et al, 2021 ; Raghu et al, 2021 ). Few years ago, Sadigh-Eteghad et al (2020) found that chronic cotinine ameliorated learning and memory in aged animals in the MWM and novel object recognition (NOR) tasks ( Sadigh-Eteghad et al, 2020 ), and also increased the expression of (a) antioxidant factors such as the superoxide dismutase (SOD), (b) synaptic proteins (PSD95, GAP-43, and synaptophysin), (c) neurotrophic factors brain-derived neurotrophic factor (BDNF), and neural growth factor (NGF), while decreasing cytokines (TNFα and IL1β) in the hippocampus of aged mice ( Sadigh-Eteghad et al, 2020 ).…”
Section: Role Of the Nachrs In Learning And Memorymentioning
confidence: 99%
“…This fungus is primarily found in the Tibetan Plateau and surrounding regions, including Qinghai, Tibet, Gansu, Sichuan, and Yunnan provinces in China, as well as certain areas in Bhutan and Nepal, typically at altitudes ranging from 3500 to 5000 m [ 2 ]. Modern pharmacological studies have revealed its diverse biological activities, such as hepatorenal protection has, for example revealed its diverse biological activities; hepatorenal protection [ 3 , 4 ], immunomodulation [ 5 ], anti-aging [ 6 ], anti-inflammatory [ 7 ], and anti-tumor effects [ 8 ]. However, due to its highwater content, a suitable drying method is essential to preserve the nutritional value, efficacy, and taste of Cordyceps sinensis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 Chemobrain or chemofog, chemotherapy-induced cognitive dysfunction, is widely recognized as a common adverse reaction following the administration of chemotherapeutic drugs. 3 More than 75% of cancer patients suffered from it. 4 Its clinical manifestations include forgetfulness, trouble with multi-tasking and executing tasks, learning difficulties, memory problems, and poor attention span.…”
Section: Introductionmentioning
confidence: 99%